Effects of single and combined exposures of gold (nano versus ionic form) and gemfibrozil in a liver organ culture of Sparus aurata - Barreto, A. (2022)
In vitro methods have gained rising importance in ecotoxicology due to ethical concerns. The aim of this study was to assess the single and combined in vitro effects of gold, as nanoparticle (AuNPs) and ionic (Au+) form, and the pharmaceutical gemfibrozil (GEM). Sparus aurata liver organ culture was exposed to gold (4 to 7200 μg·L−1), GEM (1.5 to 15,000 μg·L−1) and combination 80 μg·L−1 gold +150 μg·L−1 GEM for 24 h. Endpoints related with antioxidant status, peroxidative/genetic damage were assessed. AuNPs caused more effects than Au+, increasing catalase and glutathione reductase activities and damaging DNA and cellular membranes.